ANTIOXIDANT ACTIVITY POTENCY OF CHITOSAN FROM HARUAN (CHANNA STRIATA) SCALES - Deby Kania Tri Putri; Beta Widya Oktiani; Candra Candra; Rosihan Adhani (FKG Unlam, 2020)
ABSTRACTBackground: Stimulation of inflammatory cells such as polymorphonuclear cells (PMN) will initiate to release free radicals in destroying bacteria. Excessive free radicals can damage cells in the body. Antioxidants as one of the body's defense systems will neutralize existing free radicals. Chitosan from Haruan scales in addition to being antimicrobial turned out to also be antioxidants. Objective: To know the antioxidant potential of chitosan from haruan (Channa striata) scales. Methods: This study is a pure experimental (true experimental design) with a post-test only with control group design using two treatment groups, with quantitative tests to calculate the amount of antioxidant activity of chitosan from fish scales using DPPH radical reduction method. The first treatment is 4, 6, 8 and 10 ppm standard ascorbic acid concentration with DPPH solution as positive control, and the second treatment is 200, 250, 300 and 350 ppm chitosan from Haruan scales concentration with DPPH solution. Results: The results showed that chitosan from Haruan fish scales have antioxidant activity with 50.513% percentage of inhibition at a maximum concentration of 350 ppm with an IC50 value of 356.98 ppm. The results of the independent T-test showed that there was a significant difference between the inhibition percentage of chitosan from haruan fish scales and the inhibition percentage of ascorbic acid (p = 0,000) (p <0.05). Conclusion: Chitosan from Haruan fish scales proved to have antioxidant activity.Keywords: Antioxidants, Chitosan, Haruan fish scalesABSTRACTBackground: Stimulation of inflammatory cells such as polymorphonuclear cells (PMN) will initiate to release free radicals in destroying bacteria. Excessive free radicals can damage cells in the body. Antioxidants as one of the body's defense systems will neutralize existing free radicals. Chitosan from Haruan scales in addition to being antimicrobial turned out to also be antioxidants. Objective: To know the antioxidant potential of chitosan from haruan (Channa striata) scales. Methods: This study is a pure experimental (true experimental design) with a post-test only with control group design using two treatment groups, with quantitative tests to calculate the amount of antioxidant activity of chitosan from fish scales using DPPH radical reduction method. The first treatment is 4, 6, 8 and 10 ppm standard ascorbic acid concentration with DPPH solution as positive control, and the second treatment is 200, 250, 300 and 350 ppm chitosan from Haruan scales concentration with DPPH solution. Results: The results showed that chitosan from Haruan fish scales have antioxidant activity with 50.513% percentage of inhibition at a maximum concentration of 350 ppm with an IC50 value of 356.98 ppm. The results of the independent T-test showed that there was a significant difference between the inhibition percentage of chitosan from haruan fish scales and the inhibition percentage of ascorbic acid (p = 0,000) (p <0.05). Conclusion: Chitosan from Haruan fish scales proved to have antioxidant activity. Keywords: Antioxidants, Chitosan, Haruan fish scales.